The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12935-016-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

The BH3 mimetic drug ABT-737 induces apoptosis and acts synergistically with chemotherapeutic drugs in thyroid carcinoma cells

Abstract: Background:Patients with dedifferentiated and anaplastic thyroid carcinomas that do not take up radioiodine are resistant to chemotherapeutic treatment and external irradiation and thus are difficult to treat. Direct induction of apoptosis is a promising approach in these apoptosis-resistant tumor cells. The BH3 mimetic ABT-737 belongs to a new class of drugs that target anti-apoptotic proteins of the BCL-2 family and facilitate cell death. The purpose of this study was to investigate the effect of ABT-737 alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…Induction of apoptosis is one of the active strategies to arrest proliferation of cancer cells. Many chemical agents, such as tamoxifen, exert their anticancer effects by inducing apoptosis and they have been used to treat many types of cancers especially breast cancer [55][56][57]. Thus the anticancer activity observed with all the investigated compounds isolated from the Mediterranean soft coral E. singularis may be related to their prominent apoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis is one of the active strategies to arrest proliferation of cancer cells. Many chemical agents, such as tamoxifen, exert their anticancer effects by inducing apoptosis and they have been used to treat many types of cancers especially breast cancer [55][56][57]. Thus the anticancer activity observed with all the investigated compounds isolated from the Mediterranean soft coral E. singularis may be related to their prominent apoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…ABT‐737, a small molecule that occupies the BH3 binding pocket of Bcl‐2, exhibits an antitumor effect on several types of tumors dependent on Bcl‐2 [Kelly et al, ; Broecker‐Preuss et al, ; Roberts et al, ]. Of all the putative BH3 mimetics tested, only ABT‐737 acted similarly to Bcl‐2 by indirectly activating Bax/Bak‐dependent mitochondrial apoptosis [van Delft et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…ABT-737 is a BH-3 mimetic that interacts and inhibits Bcl-2, and has been previously shown to be an inducer of cancer cell apoptosis (7,8). This mimetic can inhibit the anti-apoptotic Bcl-2 family of proteins (i.e., Bcl-xL, Bcl-2, and Bcl-w), but has a lower effect on Mcl-1 proteins (9,10). Previous research has demonstrated that ABT-737 has a potent single-agent activity or can act synergistically with other chemotherapeutic drugs against various types of hematological malignancies and solid tumors, such as melanoma cells, glioma cells (11), acute myeloid leukemia, chronic lymphocytic leukemia, malignant lymphomas, multiple myelomas, acute lymphoblastic leukemia, and on solid tumors (12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from other groups indicate that the mitochondrial apoptotic pathway may be involved in the action of ABT-737 and DDP (19). Apoptosis is composed of two signaling pathways: the extrinsic or death receptor pathway, which is regulated by combining extracellular ligands of the tumor necrosis factor (TNF) family with death receptors, and the intrinsic or mitochondrial pathway, which is controlled by proteins of the B-cell lymphoma (Bcl-2) family (i.e., Bcl-xL, Bcl-w, Mcl-1, Bax, Bak, Bid, Noxa, Puma, and Bim) (9). Interactions and the balance between pro-survival and proapoptotic members could determine the cell's fate (11).…”
Section: Introductionmentioning
confidence: 99%